2013
DOI: 10.1016/j.jss.2013.01.032
|View full text |Cite
|
Sign up to set email alerts
|

Postoperative complications and implications on patient-centered outcomes

Abstract: Background Postoperative complications increase patient morbidity and mortality and are a target for quality improvement programs. The goal of this study was to review the world's literature on postoperative complications in general surgery patients and to try to examine the effect of these complications on patient-centered outcomes. Methods A comprehensive search of the current literature identified 18 studies on the topic of postoperative complications in general surgery patients. Results Postoperative c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
110
1
3

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 154 publications
(117 citation statements)
references
References 28 publications
3
110
1
3
Order By: Relevance
“…It is also frequently used as a proxy for quality of care for surgical patients and may come under increased scrutiny as our healthcare delivery paradigm continues to evolve. Postoperative complications are known to increase the length of stay significantly [25]; however, our analysis shows preoperative MI to be an independent predictor of prolonged length of stay even after additional adjustment for complications (five days vs. four days).…”
Section: Discussioncontrasting
confidence: 62%
“…It is also frequently used as a proxy for quality of care for surgical patients and may come under increased scrutiny as our healthcare delivery paradigm continues to evolve. Postoperative complications are known to increase the length of stay significantly [25]; however, our analysis shows preoperative MI to be an independent predictor of prolonged length of stay even after additional adjustment for complications (five days vs. four days).…”
Section: Discussioncontrasting
confidence: 62%
“…The perioperative period contains significant risk, where clinical instability is the norm more than the exception 1,2 . Up to 43% of surgical patients may exhibit some kind of perioperative complication [3][4][5][6][7][8][9][10][11][12][13][14][15][16] , and short-term morbidities are associated with longer-term outcomes. A recently published manuscript has demonstrated that perioperative mortality is the third leading cause of death internationally 17 .…”
Section: Introductionmentioning
confidence: 99%
“…Although perioperative care can help prevent these complications 4,18 , clinicians often struggle to identify those patients at highest risk of complications without performing time-consuming chart reviews 19 . This has led to the adoption of risk scoring systems 20,21 ; however, most current risk scores are focused on individual complications 22,23 , and tend to use simplistic point systems to allow for easy application 21,22 .…”
Section: Introductionmentioning
confidence: 99%
“…4 Despite advances made in understanding factors that elevate surgical risk and the widespread uptake of quality improvement initiatives, limited progress has been made in circumventing increased hospital costs of care that directly result from postoperative morbidity. Patient-centered outcomes of care are emerging as a metric within various surgical disciplines, 5 providing an opportunity to evaluate contributors to increased costs of care, one of which is the cost of hospital readmissions. In June 2009, the Centers for Medicare and Medicaid Services began acknowledging rates of 30-day readmission, thereby highlighting the importance of hospital readmission as an important quality metric.…”
mentioning
confidence: 99%